The study of permanent problems of pharmacist's protocol realization concerning wet cough - O. Yu. Horodnycha; Kh. I. Makukh; A. B. Zimenkovsky (The State Expert Center of the Ministry of Health of Ukraine, 2021)
Cough is a typical symptom of common cold and a frequent reason for visiting the pharmacies and purchasing over-the-counter (OTC) medicines. Dispensing drugs for the symptomatic relief of cough is carried out in accordance with the current pharmacist's protocol, which describes the algorithm of pharmaceutical care. Aim of the study - to determine the permanent problems of pharmacist's protocol realization concerning wet cough by questionnaire survey of pharmacy workers. The study was carried out by 2 steps: step 1 - in 2015 (May-December), step 2 - in 2020 (January-October). One developed questionnaire was used for both steps of the research process. 168 of pharmacy employees took part in step 1, and 144 - in step 2. Methods: systemic approach, questionnaire survey, analytical, statistical and comparative. It was found that 75,6% of pharmaceutical workers in 2015 and 97,2% in 2020 (p < 0,05) asked pharmacy customers about «threatening» symptoms in patients with cough. If any «threatening» symptom was identified, 73,2% of respondents in 2015 compared with 96,4% in 2020 referred patients to a doctor (p < 0,05), 18,9% vs 29,3% of respondents recommended and dispensed antibiotics (p < 0,05), 13,4% vs 19,3% - antiviral drugs (p > 0,05), 18,1% vs 65,7% - analgesics-antipyretics/non-steroidal anti-inflammatory drugs (p < 0,05), 3,1% vs 37,1% - vitamin and mineral complexes (p < 0,05). Acetylcysteine (76,2% of respondents in 2015 vs 89,6% in 2020, p < 0,05) and ambroxol (59,5% of respondents in 2015 vs 84,7% in 2020, p < 0,05) were the most frequently recommended and dispensed medicines from pharmacies for symptomatic pharmacotherapy of wet cough. At the same time, 11,3% of respondents in 2015 vs 8.3% in 2020 (p > 0.05) still dispensed antitussive drugs which are contraindicated in this case. In 2015 priority was given to syrups (85,1%) and tablets for oral administration (62,5%), but in 2020 - sachets (80,6%) and tablets for oral administration (79,9%). However, 8,3% of pharmacy workers in 2015 vs 15,2% in 2020 never interviewed pharmacy customers regarding co-morbidity in patients (p > 0.05). Quality and safety of drugs were the most important motivating factors in OTC-drugs choice at both steps of the study. In 2020 their influence on the choice of OTC-drugs increased significantly (p < 0.05). According to the results of the questionnaire survey, 5 main permanent problems associated with the pharmacist's protocol realization concerning wet cough have been identified, the solution of which will improve the quality of pharmaceutical care in pharmacies.